Penerapan Model Talking Stick untuk Meningkatkan Hasil Belajar pada Materi Matematika Satuan Waktu di Kelas III MI Cibuntu - Nurkaidah Nurkaidah; Dwi Kartika Susanti (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
Mathematics is an important science. Therefore mathematics needs to be applied early on in children. before the research, in adding hours, minutes and seconds in Grade III MI Cibuntu using the equivalence technique of hours, minutes and seconds. It turned out that after this technique was implemented in grade III, the learning outcomes achieved by students were always unsatisfactory with an average evaluation result of only reaching 57, and some students actually experienced difficulties with obtaining scores far below the KKM mathematics score that had been set, namely 65. The problem Another thing that arises is the length of time to complete. For this reason, a research was conducted entitled